An investigation into the visualisation of the transmission network by national grid controllers - Lazanas, Panagiotis (My University, 2006)
The South African electrical utility,ESKOM, is one of the largest in the world with 40 GW capacity, worth R 965 billion, and an annual income of R 33 billion. The people responsible for the voltage control of the ESKOM transmission grid are highly skilled voltage controllers. An investigation was conducted to identify what constitutes their expertise. This is a ultidisciplinary research project that incorporates the fields of Power System Engineering, Industrial and Cognitive Psychology and Neuro-Linguistic Programming. Observations of the voltage controllers at work were carried out followed by in-depth interviews in order to identify, their Mental Control Strategies, Power System Visualization techniques, and Mental Models. Expert and novice voltage controllers were included in the research as well as one in-house Man Machine Interface (MMI) developer. Some of the main findings are: ·The sophisticated mental strategies that allow controllers to simplify the overabundance of data presented to them. ·The subconsciously created vivid mental imagery that they use to make fast intuitive decisions. Having obtained the above information, MMI design and human controller training can be optimised.
Faculty of Engineering & Built Environment, School of Electrical & Infomation Engineering, MSC Dissertation
Keywords: Power System Visualization; Mental Models; Power System; Operation; Operator Mental Models; Cognitive Systems Engineering